2020
DOI: 10.1007/s12928-020-00651-9
|View full text |Cite
|
Sign up to set email alerts
|

Details on the effect of very short dual antiplatelet therapy after drug-eluting stent implantation in patients with high bleeding risk: insight from the STOPDAPT-2 trial

Abstract: Previously we briefly reported the effect of 1-month dual antiplatelet therapy (DAPT) for patients with high bleeding risk (HBR) receiving percutaneous coronary intervention (PCI) in the STOPDAPT-2 trial, but full analysis data has not been available. We conducted post-hoc subgroup analysis regarding the effect of very short DAPT for HBR patients in STOPDAPT-2 trial. The primary endpoint was a 1-year composite of cardiovascular (cardiovascular death, myocardial infarction, definite stent thrombosis, or stroke)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 23 publications
2
45
1
Order By: Relevance
“…Moreover, compared with the STOPDAPT 2 20 study from East Asia and a Swiss study, 18 the 1-year incidence of BARC type 3 or 5 bleeding in HBR patients in this study was relatively low (1.4% in our study compared to 3.26% in the STOPDAPT 2 study and 6.4% in the Swiss study).…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, compared with the STOPDAPT 2 20 study from East Asia and a Swiss study, 18 the 1-year incidence of BARC type 3 or 5 bleeding in HBR patients in this study was relatively low (1.4% in our study compared to 3.26% in the STOPDAPT 2 study and 6.4% in the Swiss study).…”
Section: Discussioncontrasting
confidence: 67%
“…For such HBR patients, the optimal intensity and duration of DAPT represent a remarkable challenge. [21][22][23][24] Nevertheless, the rate of DAPT discontinuation was relatively lower compared with that recommended in the current guideline and not different between the HBR and non-HBR groups during the long follow-up period. This tendency was in line with that in a large multicenter trial in Japan and it may be explained the fear of ST in the first-generation DES era, which lasted number of ARC-HBR major or minor criteria increased (≥2 majors: 24.3%, 1 major: 17.0%, ≥2 minors: 11.7%, non-HBR: 5.7%, P<0.0001).…”
Section: Clinical Outcomesmentioning
confidence: 56%
“…A subanalysis of the STOPDAPT-2 trial 46 also reported the results of a comparison between HBR and non-HBR patients stratified by the ARC-HBR criteria, suggesting that the benefit of 1 month of DAPT over 12 months of DAPT was greater in HBR patients. 8 These results indicated, both at the registry level and clinical trial level, that the ARC-HBR criteria can be adequately applied in Japan.…”
Section: Are the Arc-hbr Criteriamentioning
confidence: 90%
“…There are also reports that support the application of the HBR concept in Japanese patients. 7,8 For these reasons, we have adopted the HBR concept 5,6 as a basic strategy. In addition, a Japanese version of the HBR criteria that takes into account risk factors such as low body weight, frailty, heart failure, and dialysis was proposed by consensus among the guideline development team.…”
Section: A Consensus Document By the Academic Researchmentioning
confidence: 99%